Proposal for the Characterization of Agrarian Cooperatives and Solidarity Enterprises of Baixo Tocantins in Pará State, Brazil - Gómez López, José Daniel; Ortiz Pérez, Samuel (Cooperativismo & Desarrollo, 2014)
This article is the result of extensive field work fundamentally focused on the organization of small family producers through agrarian cooperatives in the Baixo Tocantins region (Pará State, Brazil). This type of socioeconomic structure in progressive expansion in the territory under study implies real improvement, not only in its social but also material and cultural aspects, both for the partners–farmers and their families and for the communities where the cooperatives are located and carry out their activities. This substantial improvement has been verified in the territory under study and is reflected in a significant increase in family income, the introduction of new practices and techniques that try to be respectful of the environment and sustainable over time, greater sovereignty in farming practices and decision-making, a noteworthy independence from traditional commercial circuits (intermediation) and the feasibility of rural life for future generations through cooperative territorialisation.